DETERMINAN TINGKAT KOMPETENSI TANGGAP BENCANA PERAWAT - Naomi Gracya Saur Rotua (2022)
Adequate readiness and competence are needed by nurses considering nurses are the largest members of the health team and have an important role in dealing with disasters. This suboptimal competence of nurses will have an impact, namely increasing the number of victims, causing delays and inability to carry out the evacuation process and not meeting the needs of the victims, as well as the death of health professionals. This study aims to analyze the determinants of the competency level of nurses in disaster response. The research method used is Cross Sectional by using the Chi Square test to with 220 samples obtained by the Multistage Sampling method. The research instrument used is a questionnaire that has been tested for validity and reliability. This study found that the related factors were age (p-Value = 0.012), last education (p-Value = 0.000), disaster assignment experience (p-Value = 0.000), disaster and/or emergency training (p-Value = 0.001), awareness of the availability of disaster management guidelines (p-Value = 0.009). While the unrelated factors are gender (p-Value = 0.155), length of work (p-Value = 0.430) and work unit (p-Value = 0.185). The conclusion of this study is that education and training are needed to improve the competence of disaster response nurses. In addition, experience in disaster assignment and awareness regarding the availability of disaster management guidelines can be a supporting factor in increasing nurses' competence in disaster response.